2020
DOI: 10.3390/foods9101394
|View full text |Cite
|
Sign up to set email alerts
|

Interface Compositions as Determinants of Resveratrol Stability in Nanoemulsion Delivery Systems

Abstract: The incorporation of hydrophobic ingredients, such as resveratrol (a fat-soluble phytochemical), in nanoemulsions can increase the water solubility and stability of these hydrophobic ingredients. The nanodelivery of resveratrol can result in a marked improvement in the bioavailability of this health-promoting ingredient. The current study hypothesized that resveratrol can bind to caprine casein, which may result in the preservation of the biological properties of resveratrol. The fluorescence spectra provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, a caprine-surfactant combination has been found ideal over bovine-surfactant complex in stabilising nanoemulsion incorporated by resveratrol. Further studies to describe the chemical degradation of resveratrol in nanoemulsion distribution systems stabilised by emulsifiers (caprine casein, polysorbate-20) and hydrocolloids (polysaccharides) are highly necessary; they can alter the structure and composition of the adsorbed stabilising substrate, with significant consequences for texture and shelf life [180]. Casein complexes with polysaccharides is an emerging interest in developing novel emulsifiers and stabilisers as casein can adsorb on the surface of oil-water emulsion.…”
Section: Caseins and Nano Emulsionsmentioning
confidence: 99%
“…However, a caprine-surfactant combination has been found ideal over bovine-surfactant complex in stabilising nanoemulsion incorporated by resveratrol. Further studies to describe the chemical degradation of resveratrol in nanoemulsion distribution systems stabilised by emulsifiers (caprine casein, polysorbate-20) and hydrocolloids (polysaccharides) are highly necessary; they can alter the structure and composition of the adsorbed stabilising substrate, with significant consequences for texture and shelf life [180]. Casein complexes with polysaccharides is an emerging interest in developing novel emulsifiers and stabilisers as casein can adsorb on the surface of oil-water emulsion.…”
Section: Caseins and Nano Emulsionsmentioning
confidence: 99%
“…Table 2 presents the average droplet size of the luteinloaded emulsions prepared with the biopolymer system of casein (bovine, caprine), yeast β-glucan, and maltodextrin. These results clearly indicate the excellent emulsifying properties of these milk proteins, which include reducing the interfacial tension and the rapid absorption at the oil-water interface during emulsion preparation [23,24]. Low interfacial tension at the oil-water interface is of paramount importance to obtain dispersions with small average droplet size and hence good physical stability.…”
Section: Physical Properties Of Emulsionsmentioning
confidence: 83%
“…It has been previously reported that caprine α s1 -I casein and caprine α s1 -II casein appear to bind to lutein, thereby improving stability of lutein [23]. Such differences in β-casein content exhibited by the caprine α s1 -I casein and caprine α s1 -II casein were also reflected in the improved stability of resveratrol in oil-in-water emulsions [24].…”
Section: Characterization Of Bovine and Caprine Caseinsmentioning
confidence: 88%
See 1 more Smart Citation
“…The standard calibration curve was plotted using RESV (0.5–5 µg/mL) with a correlation coefficient of 0.999. The RT of trans-resveratrol was around 2.817 min [ 15 ].…”
Section: Methodsmentioning
confidence: 99%